2011
DOI: 10.1007/s11771-011-0786-3
|View full text |Cite
|
Sign up to set email alerts
|

Bonding mechanism of X10CrNi18-8 with Ni/Al2O3 composite ceramic by pressureless infiltration

Abstract: An alloy steel/alumina composite was successfully fabricated by pressureless infiltration of X10CrNi18-8 steel melt on 30% (mass fraction) Ni-containing alumina based composite ceramic (Ni/Al 2 O 3 ) at 1 600 °C. The infiltration quality and interfacial bonding behavior were investigated by SEM, EDS, XRD and tensile tests. The results show that there is an obvious interfacial reaction layer between the alloying steel and the Ni/Al 2 O 3 composite ceramic. The interfacial reactive products are (Fe x Al y ) 3 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 11 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The flexural strength and fracture toughness were much higher than pure Al 2 O 3 ceramics. Yang et al [6] reported that alloy steel and ceramic composite materials were used a pressure-free infiltration process, and added nickel to them in order to significantly improve the wettability between them. Zhou et al [7] prepared a honeycomb structure ZTA preform reinforced HCCI composites by infiltration method, which can effectively improve its wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The flexural strength and fracture toughness were much higher than pure Al 2 O 3 ceramics. Yang et al [6] reported that alloy steel and ceramic composite materials were used a pressure-free infiltration process, and added nickel to them in order to significantly improve the wettability between them. Zhou et al [7] prepared a honeycomb structure ZTA preform reinforced HCCI composites by infiltration method, which can effectively improve its wear resistance.…”
Section: Introductionmentioning
confidence: 99%